The Effect of Salary Satisfaction and Incentives on The Performance of Crew Vessel at PT. Maritim Barito Perkasa in Banjarmasin - Suwestian, M. Firdaus; Yusuf, Muhammad (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The purpose of the study was to determine and analyze the effect of salary satisfaction and incentives, partially and simultaneously, on the performance of crew vessel PT. Maritim Barito Perkasa in Banjarmasin. This study is a quantitative descriptive study using 90 respondents from crew vessels at PT. Maritim Barito Perkasa. The data analysis used is multiple linear regression analysis. The results of the study indicate that the salary satisfaction and the incentive factor has a significant effect on the performance factor of crew vessels of PT. Maritim Barito Perkasa in Banjarmasin. Simultaneously, the salary satisfaction factor and incentive satisfaction have a significant effect on the performance factor of crew vessels of PT. Maritim Barito Perkasa in Banjarmasin.